The level of tolerance for political belligerents among household heads in Lawaan, Eastern Samar. - Gonzaga, Angelyn (Tacloban City Angelyn Gonzaga [and] Ma. Bernadette T. Inciso, 2010)
This research study is centered on the municipality of Lawaan, eastern Samar. It has sixteen barangays all in all, comprising a total population of 11, 302. Lawaan lies between the municipalities of Marabut, Samar and Balangiga, Eastern Samar. Moreover, it faces the Lawaan Bay but is mountainous at the same time.
For years, the particular island of Samar has been one of the hot spots and is continuously threatened by the presence of some belligerent groups. Despite government efforts against these groups, the growth of the number of its members continues to increase. It is indeed noteworthy to tell that a number of studies have already been conducted exploring the nature and dynamics of political stability, as well as the government's action in response to its continuous expansion of influence on the Filipino people. This study sought to determine the level of tolerance for political belligerents of the household heads in Lawaan, E. Samar. Furthermore, it also aimed to determine the socio-demographic profile of the people of Lawaan. This also sought to determine the relationship between the socio-demographic profile of the people of Lawaan and their level of tolerance on the presence of the belligerent groups.
The researchers of this study utilized a self-administered questionnaire as a major instrument during the data gathering. This study also made use of a structured interview to substantiate the answers provided by the respondents in the questionnaire.
This study found out that the support of the people for the belligerents and the government against these belligerents are both on the average level. In other words, their level of tolerance for the belligerent groups is on the average level. This is moreover influenced by the respondents' respective socio-demographic characteristics. The study showed that there is a significant relationship between age and the respondents' level of tolerance. On the other hand, respondents' gender, occupation and educational attainment have no significant relationship with their level of tolerance on belligerents.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science